2005
DOI: 10.1053/j.gastro.2004.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Liver regeneration, growth factors, and amphiregulin

Abstract: The sequence of events triggering liver regeneration after acute loss of hepatic mass has been the subject of much investigation during the past 20 years. 1 Rapid changes in gene expression and activation of receptors and transcription factors occur immediately after partial hepatectomy (PHx). 2,3 Several potential signaling stimuli are released in the liver or in circulation after the loss of hepatic parenchyma. These stimuli have effects on liver and on hepatocytes (or other hepatic cells) in culture. Such s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 23 publications
3
92
0
11
Order By: Relevance
“…Numerous growth factors and cytokines have been implicated in the initiation and control of this regenerative response [1,[10][11][12][13][14][15][16], with the activation of seemingly critical transcription factors, such as AP-1, NFκB and STAT-3. Liver injury can be associated with a defective intestinal barrier, leading to exposure to bacterial products such as lipopolysaccharides and components of the innate immune system (complement fragments), and their activation of the NFκB pathway in Kupffer cells, leading to the production and secretion Figure 1.…”
Section: Hepatocytesmentioning
confidence: 99%
“…Numerous growth factors and cytokines have been implicated in the initiation and control of this regenerative response [1,[10][11][12][13][14][15][16], with the activation of seemingly critical transcription factors, such as AP-1, NFκB and STAT-3. Liver injury can be associated with a defective intestinal barrier, leading to exposure to bacterial products such as lipopolysaccharides and components of the innate immune system (complement fragments), and their activation of the NFκB pathway in Kupffer cells, leading to the production and secretion Figure 1.…”
Section: Hepatocytesmentioning
confidence: 99%
“…Cell cycle progression is driven by growth factors, especially by hepatocyte growth factor (HGF) and the epidermal growth factor receptor ligand family, which can activate various mitogenic signaling pathways, including extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), phosphoinositide-3 kinase, and S6 kinase. 3,4 Signaling cascades triggered by cytokines and growth factors have been extensively studied because they seem to play central roles in liver regeneration after PH. 5 Recently, it has been demonstrated that liver regeneration is also tightly regulated by physiological functions of the liver, such as lipid 6,7 and bile acid 8 metabolism.…”
mentioning
confidence: 99%
“…Following this priming phase, cell cycle progression is then dependent on growth factors, such as hepatocyte growth factor (HGF), transforming growth factor-alpha (TGF-α) and epidermal growth factor (EGF) [56,57] . The two main growth-promoting signaling systems involved in liver regeneration are the HGF and its receptor (Met) and the epidermal growth factor receptor (EGFR) and its relatively large family of ligands.…”
Section: Growth Factors and Growth-factor Signaling Systems In Livermentioning
confidence: 99%
“…EGF is mainly produced in the salivary glands in rodents and plays an important role in hepatocyte proliferation by binding to the EGFR on hepatocytes [57] . Sialoadenectomy-induced decrease in circulating EGF in mice and rat models resulted in impaired liver regeneration following partial hepatectomy, which was reversed by the administration of EGF [70,71] .…”
Section: Growth Factors and Growth-factor Signaling Systems In Livermentioning
confidence: 99%
See 1 more Smart Citation